2013
DOI: 10.1177/0300060513476438
|View full text |Cite
|
Sign up to set email alerts
|

Complications following dorsal versus volar plate fixation of distal radius fracture: A meta-analysis

Abstract: Dorsal fixation offers a lower risk of neuropathy and carpal tunnel syndrome than the volar approach, but a higher risk of tendon irritation. Patients with a distal radius fracture can expect similar outcomes after volar or dorsal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 24 publications
(62 reference statements)
1
66
1
Order By: Relevance
“…However, patients who were treated with dorsal plate fixation had higher risk of tendon problems. 49 In our study, no significant differences were reported in complication rates between dorsal and volar plate fixation. In our opinion, the decision for the type of fixation should be based on the type of malunion and the surgeon's experience with the specific approach and technique.…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…However, patients who were treated with dorsal plate fixation had higher risk of tendon problems. 49 In our study, no significant differences were reported in complication rates between dorsal and volar plate fixation. In our opinion, the decision for the type of fixation should be based on the type of malunion and the surgeon's experience with the specific approach and technique.…”
Section: Discussioncontrasting
confidence: 49%
“…48 Recently, a meta-analysis was published that evaluates complications in distal radius fractures treated with dorsal or volar plate fixation. 49 No significant differences were observed in the overall complication risk. 49 Patients with volar plate fixation showed a higher rate of neuropathy and carpal All data are expressed in percentages.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Despite the development of new low profi le implants, tendon irritation or rupture remains one of the most frequent complication after dorsal plating (19). Tendon rupture has been reported as early as 8 weeks and as late as 7 months after the surgery (20).…”
Section: Introductionmentioning
confidence: 99%
“…5,6,20,21) The palmar cutaneous branch of the median nerve lies close to the FCR sheath and various anatomical variations in its origin and course render it vulnerable to injury during surgical approaches in this area. 5,10,11,13,14,[22][23][24][25] The most common manifestations of a PCBMN injury in our series were parasthesiae, hypoaesthesia or anaesthesia in the distribution of the nerve coupled with pain on extension of the wrist.…”
Section: )mentioning
confidence: 99%